Estimation of the Parameter of an Exponential Distribution When Applying Maximum Likelihood and Probability Plot Methods Using Simulation - Hamad, A.M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Exponential Distribution is probably the most important distribution in reliability work. In this paper, estimating the scale parameter of an exponential distribution was proposed through out employing maximum likelihood estimator and probability plot methods for different samples size. Mean square error was implemented as an indicator of performance for assumed several values of the parameter and computer simulation has been carried out to analysis the obtained results